The Nation-State as the Order of the United States: Westphalia, Regimes of Truth, and Global Power Post-1945 - Maya, Arthuur Jeverson; Wene, Adrianus Lengu (Ridwan Institute, 2026)
This article examines the nation-state not as a neutral political entity or the natural evolution of modernity, but as a historical construct engineered and stabilized through post–World War II global power relations. Using a genealogical approach, this article argues that the Westphalia system did not remain a legacy of 17th-century Europe but was reformulated and operated by the United States as a global order that produced a regime of truth about sovereignty, legitimacy, and political acceptance. Through the institutionalization of the United Nations, the Bretton Woods system, NATO, and a network of international legal, economic, and security standards, contemporary nation-states are conditioned to function as operators in transnational governmentality rather than as autonomous political subjects. Sovereignty is symbolically defended yet materially and epistemically subjugated to the American-centric logic of power. This article also reveals the symbolic-theological dimension of this order, in which democracy and freedom operate as state faiths that legitimize intervention and the selective suspension of the principle of non-intervention. The findings of this study indicate that the post-Westphalia nation-state has undergone a fundamental functional mutation—from an instrument of political emancipation to a global disciplinary apparatus that works through normalization, the production of meaning, and symbolic surveillance.